ηN interactions in the nuclear medium. η-nuclear bound states - Mareš J. (EPJ Web of Conferences, 2016)
We report on our recent study of in-medium ηN interactions and η-nuclear quasi-bound states. The ηN scattering amplitudes considered in the calculations are constructed within coupled-channel models that incorporate the S11 N*(1535) resonance. The implications of self-consistent treatment and the role played by subthreshold dynamics are discussed.